2017
DOI: 10.1158/1940-6207.capr-17-0202
|View full text |Cite
|
Sign up to set email alerts
|

Airway Basal Cell Heterogeneity and Lung Squamous Cell Carcinoma

Abstract: Basal cells are stem/progenitor cells that maintain airway homeostasis, enact repair following epithelial injury, and are a candidate cell-of-origin for lung squamous cell carcinoma. Heterogeneity of basal cells is recognized in terms of gene expression and differentiation capacity. In this Issue, Pagano and colleagues isolate a subset of immortalized basal cells that are characterized by high motility, suggesting that they might also be heterogeneous in their biophysical properties. Motility-selected cells di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 11 publications
1
16
0
Order By: Relevance
“…The results confirm that 16HBE‐T cells develop the characteristics of LSUC consistently with data from previous epidemiological and in vitro studies 41–43 . It is also well‐known that LUSC has a tendency to occur in the bronchi, and the 16HBE used in our in vitro experiments is an immortalized cell constructed from human normal bronchial epithelial cells 44,45 . Consequently, when it is induced by BPDE to become cancerous, it is more likely to differentiate into a phenotype of LUSC.…”
Section: Discussionsupporting
confidence: 88%
“…The results confirm that 16HBE‐T cells develop the characteristics of LSUC consistently with data from previous epidemiological and in vitro studies 41–43 . It is also well‐known that LUSC has a tendency to occur in the bronchi, and the 16HBE used in our in vitro experiments is an immortalized cell constructed from human normal bronchial epithelial cells 44,45 . Consequently, when it is induced by BPDE to become cancerous, it is more likely to differentiate into a phenotype of LUSC.…”
Section: Discussionsupporting
confidence: 88%
“…[ 1 , 2 , 3 ] Lung adenocarcinoma has been postulated to originate from club cells, AT2 cells, or BASCs, while squamous cell carcinomas likely arise from basal cells. [ 4 , 5 , 6 ] Experimental models have shown that given different oncogenes, lung cells can be more or less “fit” to form fully malignant lesions. [ 7 , 8 , 9 ] However, the cellular origins for the majority of lung cancers have not been clarified yet.…”
Section: Introductionmentioning
confidence: 99%
“…Basal cells are progenitor cells closely associated with the basal lamina that maintain airway homeostasis. Basal cells are considered the candidate cell of origin in lung SqCC [6]. Although LUAD sometimes exhibits features of airway basal cells, there is no evidence that these cells can be its cell of origin [7].…”
Section: Introductionmentioning
confidence: 99%